Testing the Limits of Skill Transfer for Scrabble Experts in Behavior and Brain - van Hees, Sophia; Pexman, Penny M.; Hargreaves, Ian S.; Zdrazilova, Lenka; Hart, Jessie M.; Myers-Stewart, Kaia; Cortese, Filomeno; Protzner, Andrea B. (Frontiers in Human Neuroscience, 2016)
We investigated transfer of the skills developed by competitive Scrabble players. Previous studies reported superior performance for Scrabble experts on the lexical decision task (LDT), suggesting near transfer of Scrabble skills. Here we investigated the potential for far transfer to a symbol decision task (SDT); in particular, transfer of enhanced long-term working memory for vertically presented stimuli. Our behavioural results showed no evidence for far transfer. Despite years of intensive practice, Scrabble experts were no faster and no more accurate than controls in the SDT. However, our fMRI and EEG data from the SDT suggest that the neural repertoire that Scrabble experts develop supports task performance even outside of the practised domain, in a non-linguistic context. The regions engaged during the SDT were different across groups: controls engaged temporal-frontal regions, whereas Scrabble experts engaged posterior visual and temporal-parietal regions. In Scrabble experts, activity related to Scrabble skill (anagramming scores) included regions associated with visual-spatial processing and long-term working memory, and overlapped with regions previously shown to be associated with Scrabble expertise in the near transfer task (LDT). Analysis of source waveforms within these regions showed that participants with higher anagramming scores had larger P300 amplitudes, potentially reflecting greater working memory capacity, or less variability in the participants who perform the task more efficiently. Thus, the neuroimaging results provide evidence of brain transfer in the absence of behavioural transfer, providing new clues about the consequences of long-term training associated with competitive Scrabble expertise.